Mitochondrial Quality Control in Cardiomyocytes: A Critical Role in the Progression of Cardiovascular Diseases - Fan, Hualin; He, Zhengjie; Huang, Haofeng; Zhuang, Haixia; Liu, Hao; Liu, Xiao; Yang, Sijun; He, Pengcheng; Yang, Huan; Feng, Du (Frontiers in Physiology, 2020)
Mitochondria serve as an energy plant and participate in a variety of signaling pathways to regulate cellular metabolism, survival and immunity. Mitochondrial dysfunction, in particular in cardiomyocytes, is associated with the development and progression of cardiovascular disease, resulting in heart failure, cardiomyopathy, and cardiac ischemia/reperfusion injury. Therefore, mitochondrial quality control processes, including post-translational modifications of mitochondrial proteins, mitochondrial dynamics, mitophagy, and formation of mitochondrial-driven vesicles, play a critical role in maintenance of mitochondrial and even cellular homeostasis in physiological or pathological conditions. Accumulating evidence suggests that mitochondrial quality control in cardiomyocytes is able to improve cardiac function, rescue dying cardiomyocytes, and prevent the deterioration of cardiovascular disease upon external environmental stress. In this review, we discuss recent progress in understanding mitochondrial quality control in cardiomyocytes. We also evaluate potential targets to prevent or treat cardiovascular diseases, and highlight future research directions which will help uncover additional mechanisms underlying mitochondrial homeostasis in cardiomyocytes.